PELATIHAN PENULISAAN PENELITIAN TINDAKAN KELAS (PTK) PADA GURU SDN CIBITUNG KULON 01 BOGOR - Chrisnaji Banindra Yudha; Ilmi Noor Rahmad (LPPM Universitas Flores, 2020)
Education has the core of the interaction between educators and students in helping students master educational goals. Educational interactions can take place in the family, school, and community environment, which will support students to develop their educational experience. Classroom action research is described as an effort to examine the learning activities of students by carrying out a planned action by the teacher and analyzing the effect of actions to improve and improve the quality of learning. The activity method used in community service activities is (1) lectures, used by the service team to convey the principles of classroom action research, classroom action research procedures, implementation of classroom action research, and procedures for writing classroom action research reports. The lecture was supported by the use of laptops and LCDs to display service materials for a limited time. (2) Demonstration, used by the service team in the hope that participants can start practicing problem formulation in the learning process that can be solved through classroom action research, class action research proposal design, to writing class action research reports. The conclusion of this community service, namely (1) the community service activities carried out by the Research Team for the Primary School Teacher Education Department with the lecture and demonstration method have been able to improve the understanding of teachers of SDN Cibitung Kulon 01 Bogor about classroom action research and it is hoped that the teacher can simultaneously write the report, (2) writing reports Classroom action research is expected as an effort to develop the profession and at the same time assist teachers in achieving the credit score required for promotion.